POSITION RESOURCES OF THO CHU ISLAND GROUP, SOUTHERN VIETNAM - Ve, Nguyen Dac; Thanh, Tran Duc; Lan, Tran Dinh; Vuong, Bui Van; Huyen, Nguyen Thi Minh (Vietnam Journal of Marine Science and Technology, 2018)
Located near center of the Gulf of Thailand, the Tho Chu island group is approximately far 160 km from Ca Mau southwestwards, and 100 km from Phu Quoc island northwestwards. This group consists of 8 islands, of which the largest Tho Chu island is of 12.15 km2 wide and 167 m high, and composes of clastic sedimentary rocks. Despite the greatest distance from the coast, this coastal island group has the characteristics of geological structure, morphology, spatial structure, area, height, ecological landscape, dynamics and stability of natural processes that create the great value of geo-natural position resources and favorable residential environment. Regarding value of geo-economic position resources, the island group belongs to Phu Quoc district, but it meets the good conditions to become a district-level administrative unit belonging to Kien Giang province. This is a priority site for sea-island economic development, the island group has a great potential to develop the marine economic sectors such as fisheries, natural conservation, tourism and other important services such as oil and gas extraction, navigation and search-rescue at sea. In terms of value of geo-political position resources, this island group includes Hon Nhan islet as the basic point of A1, so has the great value for Vietnam’s sovereignty, sovereign rights and interests in the Gulf of Thailand. Situating in the politically high sensitive region, the island group possesses the high value on the defense, could develop into a firmly military outpost contributing to national defense and security at sea.